My Baby's Movements: A Stepped-Wedge Cluster-Randomised Controlled Trial of a Fetal Movement Awareness Intervention to Reduce Stillbirths. Issue 3 (March 2022) - Flenady, V.; Gardener, G.; Ellwood, D.; Coory, M.; Weller, M.; Warrilow, K. A.; Middleton, P. F.; Wojcieszek, A. M.; Groom, K. M.; Boyle, F.M.; East, C.; Lawford, H. L. S.; et al.
Abstract : (Abstracted from BJOG 2022;129:29–41) Decreased fetal movement (DFM) can indicate that a pregnancy is at risk for stillbirth. Maternal awareness and monitoring of fetal movement have been considered to be a simple, low-cost stillbirth prevention strategy.